Penerapan Taksonomi Bloom pada Pembelajaran Bahasa Di Kelas 2 SD Bali Kiddy - Nita Dewi, Ni Kadek; Suparwa, I Nyoman; Putra, Anak Agung Putu (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 27 No 1 (2020): : SeptemberDO - 10.24843/ling.2020.v27.i02.p10, 2020)
This research was conducted with the aim of knowing the operational verbs used in language learning in 2 nd grade at Bali Kiddy Primary School, knowing and describing verb learning strategies in language learning in 2 nd grade at Bali Kiddy Primary School and knowing the relationship of using the operational verbs with Bloom’s Taxonomy in language learning in 2 nd grade at Bali Kiddy Primary School. This research is a qualitative research using observation and interview methods in data collection. Research findings and analysis results show that there are 51 operational verbs used in language learning in grade 2 at Bali Kiddy Primary School which are categorized into two categories of verb according to Shopen Theory; 46 verbs classified as action verb and 5 verbs classified as process verb, as well as the verb learning strategies which are used in language learning in 2 nd grade at Bali Kiddy Primary School varies greatly. In addition, this study also found the relationship between the used of operational verbs in language learning in 2 nd grade at Bali Kiddy Primary School with Bloom’s Taxonomy. Overall, it was found that operational verbs in language learning was classified three cognitive categories namely C1 (remember) with examples of operational verbs menulis and membaca , C2 (understand) with examples of operational verbs memahami and menginterpretasi and also C3 (apply) with the example of operational verbs menggunakan and menyelesaikan .